The Ambivalent Effect of Autocratization on Domestic Terrorism - Lott, Lars; Croissant, Aurel; Trinn, Christoph (Studies in Conflict & Terrorism, 2023)
This study asks if a decline of democratic regime attributes affects the volume of domestic terrorism. We argue that different forms of autocratization may stimulate or suppress terrorist activities. Democratic backsliding may dampen domestic terrorism, while autocratic consolidation may make autocracies more vulnerable to terrorism. This study empirically tests these assumptions on time-series cross-sectional data on domestic terrorism in 182 countries between 1970 and 2020 with a difference-in-differences design. We find that democratic backsliding reduces the amount of terrorism in the short to medium term. Autocratic consolidation increases the number of terrorist attacks in the short to medium ter